Removal of Direct Yellow-12 Dye from Water by Adsorption on Activated Carbon Prepared from Ficus Racemosa L. - G. Revathi; S. Ramalingam; P. Subramaniam; A. Ganapathi (E-Journal of Chemistry)
The adsorption of direct yellow-12 dye (DY-12) by Atti leaf (Ficus racemosa) powder carbon (ATC) was carried out by varying the parameters such as agitation time, dye concentration, adsorbent dose, pH and temperature. Equilibrium adsorption data followed both Langmuir and Freundlich isotherms. Adsorption followed second-order kinetics. The adsorption capacity was found to be 6.7 mg dye per gram of the adsorbent. Acidic pH was favorable for the adsorption of DY-12. Desorption studies suggest that chemisorptions might be the major mode of adsorption.